Exchange rate determination and optimal economic policy under various exchange rate regimes - Jong, Eelke de (Berlin ; New York : Springer Verlag, 1991)
This study investigates the exchange rate movements; the theoretical and empirical studies of exchange rate determination; estimates of the non-financial sector's behavioural equations; and the determination of a small industrial country's optimal exchange rate parity rule.
Includes bibliographical references (p. [249]-265) and index.
rua 21/02/17
Loans.
Keywords: Foreign exchange; Foreign exchange - mathematical model